Ancient Order of United Workmen members, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - Curtis, Asahel, 1874-1941 (1909)
On verso of image: Degree of Honor A.O.U.W. Auxillary PH Coll 727.839 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number